Quality of Item Pool (QIP) Index: A Novel Approach to Evaluating CAT Item Pool Adequacy. - Gönülateş, Emre (Educational & Psychological Measurement, 2019)
This article introduces the Quality of Item Pool (QIP) Index, a novel approach to quantifying the adequacy of an item pool of a computerized adaptive test for a given set of test specifications and examinee population. This index ranges from 0 to 1, with values close to 1 indicating the item pool presents optimum items to examinees throughout the test. This index can be used to compare different item pools or diagnose the deficiencies of a given item pool by quantifying the amount of deviation from a perfect item pool. Simulation studies were conducted to evaluate the capacity of this index for detecting the inadequacies of two simulated item pools. The value of this index was compared with the existing methods of evaluating the quality of computerized adaptive tests (CAT). Results of the study showed that the QIP Index can detect even slight deviations between a proposed item pool and an optimal item pool. It can also uncover shortcomings of an item pool that other outcomes of CAT cannot detect. CAT developers can use the QIP Index to diagnose the weaknesses of the item pool and as a guide for improving item pools.